2017
DOI: 10.1080/10852352.2018.1385956
|View full text |Cite
|
Sign up to set email alerts
|

Community perspectives on substance use among Bhutanese and Iraqi refugees resettled in the United States

Abstract: Premigration trauma and postmigration stressors put refugees at high risk for mental health concerns, including substance use. However, there is limited systematic research on substance use in refugee communities exists. We conducted exploratory qualitative research to examine Bhutanese and Iraqi refugee perspectives related to the use of recreational substances after resettlement in the United States. Data were collected through separate focus groups with 28 Bhutanese and 22 Iraqi adult men. Focus groups were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…Findings on the Bhutanese community's negative and positive cultural coping strategies provide implications for targeted programs and services. Study findings allude to negative coping mechanisms such as alcohol, substance use, suicidal ideation, and suicide attempts, consistent with prior studies (Adhikari et al, 2015;Michaels et al, 2010;Mirza et al, 2018). Bhutanese refugees feel more comfortable seeking help from friends and family than from professionals (Chase & Sapkota, 2017), consistent with prior studies showing that this community generally views care seeking as negative and a sign of weakness (MacDowell et al, 2020).…”
Section: Discussionsupporting
confidence: 87%
“…Findings on the Bhutanese community's negative and positive cultural coping strategies provide implications for targeted programs and services. Study findings allude to negative coping mechanisms such as alcohol, substance use, suicidal ideation, and suicide attempts, consistent with prior studies (Adhikari et al, 2015;Michaels et al, 2010;Mirza et al, 2018). Bhutanese refugees feel more comfortable seeking help from friends and family than from professionals (Chase & Sapkota, 2017), consistent with prior studies showing that this community generally views care seeking as negative and a sign of weakness (MacDowell et al, 2020).…”
Section: Discussionsupporting
confidence: 87%
“…Similar motives were reported among Liberian, Karen and Bhutanese refugees [34, 44, 52]. Additionally, Iraqi refugees who use prescription painkillers in the United States reported that many Middle Eastern countries overuse pain medications, including opioid medications, even without prescriptions [44]. In another study, Syrian refugees indicated that taking substances helped them connect with people and feel like a part of their new community.…”
Section: Resultsmentioning
confidence: 74%
“…African refugees in Australia reported that traumatic experiences associated with migration, family separation, integrational conflict and a lack of education and employment were the main motives for using illicit drugs [35]. Similar motives were reported among Liberian, Karen and Bhutanese refugees [34, 44, 52]. Additionally, Iraqi refugees who use prescription painkillers in the United States reported that many Middle Eastern countries overuse pain medications, including opioid medications, even without prescriptions [44].…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Research exploring the health practices of resettled Bhutanese refugees or their interactions with the US healthcare system is limited, focusing primarily on gynecological health among Bhutanese refugee women (Lor et al, 2018;Poudel & Dyer, 2013;Haworth, Margalit, Ross, Nepal & Soliman, 2014;Kingsbury 2017;Davey & Vallianatos, 2018), health practices and perceptions specific to mental health (Mirza et al, 2018;Subedi, Li, Gurung Bizune, Dogbey, Johnson, Yun, 2015;Im & Rosenberg, 2015). Research exploring health practices and interactions with the healthcare system is more prevalent in other refugee populations.…”
Section: Introductionmentioning
confidence: 99%